2016
DOI: 10.11604/pamj.2016.23.20.8621
|View full text |Cite
|
Sign up to set email alerts
|

Rupture simultanée du ligament croisé antérieur et du ligament patellaire: à propos d’un cas

Abstract: La rupture simultanée du tendon rotulien et du ligament croisé antérieur est une lésion relativement rare. Son diagnostic peut facilement manquer lors de l'examen initial. Les options de traitement incluent la réparation immédiate du tendon rotulien avec soit la reconstruction simultanée ou différée de ligament croisé antérieur. Nous rapportons le cas d'une rupture combinée du tendon rotulien et du ligament croisé antérieur chez un jeune footballeur de 22 ans. Une approche de traitement en deux temps a été eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In presence of associated lesions such as meniscus or ligamentous injuries the decision to treat them all at the same time is a school matter. The choice of the moment of repairing all lesions is crucial [8]. According to the literature [8] [9] in case of associated ACL injury, the ACL reconstruction is certainly essential but cannot be combined with the others because of the risk of arthrofibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In presence of associated lesions such as meniscus or ligamentous injuries the decision to treat them all at the same time is a school matter. The choice of the moment of repairing all lesions is crucial [8]. According to the literature [8] [9] in case of associated ACL injury, the ACL reconstruction is certainly essential but cannot be combined with the others because of the risk of arthrofibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of the moment of repairing all lesions is crucial [8]. According to the literature [8] [9] in case of associated ACL injury, the ACL reconstruction is certainly essential but cannot be combined with the others because of the risk of arthrofibrosis. This reconstruction should be done on a cold knee away from local inflammatory phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is an agreement that immediate repair of the patellar tendon is recommended [ 9 , 10 ]. Two-staged surgical treatment is preferred by a few authors [ 11 , 12 ], but also one-staged procedures are reported to lead to satisfying functional results [ 10 , 13 , 14 ]. In this case, a one-staged surgical approach with primary suture anchor repair of the ACL and suture of the patellar tendon competes with a single repair of the patellar tendon and ACL reconstruction in a second step.…”
Section: Discussionmentioning
confidence: 99%